Root exudates and rhizosphere soil bacterial relationships of Nitraria tangutorum are linked to k-strategists bacterial community under salt stress - Pan, Yaqing; Kang, Peng; Tan, Min; Hu, Jinpeng; Zhang, Yaqi; Zhang, Jinlin; Song, Naiping; Li, Xinrong (Frontiers in Plant Science, 2022)
Plants are subjected to various biotic and abiotic stresses and respond by secreting different bioactive compounds through their root systems. The type, quantity, and distribution of plant root exudates affect the rhizosphere soil bacterial community structure. Therefore, understanding plant-soil-microbial interactions, especially microbial interactions, mediated by root exudates is essential. A short-term experiment was conducted under drought and salt stress to investigate the interaction between root exudates and Nitraria tangutorum microbial communities. We found that drought and salt stress increased rhizosphere soil pH and electrical conductivity while decreasing organic matter, total carbon, and total phosphorus content of N. tangutorum rhizosphere soil. 4-acetyl-4-(ethoxycarbonyl)-heptanedioic acid, 4-acetamidobutyric acid, and indole-3-acetic acid were the main differential metabolites of N. tangutorum under drought stress, and 4-acetyl-4-(ethoxycarbonyl)-heptanedioic acid, abscisic acid, prostaglandin A3, and 16-hydroxyhexadecanoic acid were the main differential metabolites under salt stress conditions. Salt stress further changed the N. tangutorum rhizosphere soil bacterial community structure, markedly decreasing the relative abundance of Bacteroidetes as r-strategist while increasing that of Alphaproteobacteria as k-strategist. The co-occurrence network analysis showed that drought and salt stress reduced the connectivity and complexity of the rhizosphere bacterial network. Soil physicochemical properties and root exudates in combination with salt stress affect bacterial strategies and interactions. Our study revealed the mechanism of plant-soil-microbial interactions under the influence of root exudates and provides new insights into the responses of bacterial communities to stressful environments.